Algeria intensifies efforts to adopt IPSAS standards: Concrete steps and future prospects - Bendekhis, Abdelkrim; Bendoukha, Mohammed Reda (The International tax journal, 2025)
This study aims to conduct an in-depth analysis of Algeria's journey towards adopting International Public Sector Accounting Standards (IPSAS). It seeks to understand the motivations behind this shift, evaluate the efforts made so far, and identify the challenges facing Algeria, such as resistance to change, lack of qualified personnel, and difficulty adapting to new requirements. The study employs a comprehensive research methodology to highlight the importance of this transformation in enhancing transparency and accountability in public financial management and to provide practical recommendations to support it. Adopting IPSAS represents a significant shift in public accounting in Algeria, contributing to the establishment of a more sustainable and transparent financial system. It is expected to enhance trust between the government, citizens, and international entities, thereby supporting economic stability and sustainable development in Algeria.